Three Essays on Monetary Union in West Africa - Adjalala, Toyimi Médès Frida (Université d'Ottawa / University of Ottawa, 2020)
Chapter 1- How well-off or worse-off a country can be by joining a currency union in the presence of structural heterogeneity and idiosyncratic shocks? In light of the proposed creation of a currency union for the Economic Community of the West African States (ECOWAS), we develop a three-region DSGE model to explore the question. We divide the ECOWAS into three regions-Nigeria, the existing WAEMU (West-African Economic Monetary Union), and the rest. Considering two monetary regimes (monetary union and monetary independence), we assess the heterogeneity in the responses to country-specific productivity and terms-of-trade shocks in these two regimes, as well as the costs related to the loss of monetary independence. Our results indicate that shocks hitting a given region generate cross-border spillover effects, whose sign and magnitude depend not only on the nature of the disturbance but also on its origin and on the monetary policy regime considered. Moreover, the propagation of shocks across regions is magnified under the monetary union regime. Shocks hitting Nigeria's economy tend to have a more destabilizing effect on the other regions, especially when they are inside the union. Our results also suggest that the proposed monetary union for the ECOWAS region can potentially lead to welfare improvement for all the members, but the magnitude of the welfare gain is relatively small. Chapter 2- In this chapter, we develop a multi-region New-Keynesian Dynamic Stochastic General Equilibrium (DSGE) of the West-African countries to provide a quantitative analysis of intergovernmental fiscal transfers in the context of the proposed creation of a monetary union. We assess the potential role of fiscal transfers in the stabilization of business cycle fluctuations in the projected monetary union in the presence of idiosyncratic shocks. Starting from a baseline scenario with no fiscal transfers among the regions, we analyze the dynamic and welfare impacts of full and partial fiscal equalization schemes with nominal tax revenue sharing within the union. We consider adverse productivity and term-of-trade shocks. Our simulation results suggest that the transfer mechanism is an efficient stabilizing tool. However, the stabilization property of the fiscal transfer system hinges upon the full or partial nature of the compensation system. Moreover, the ability of the transfer system to absorb the negative effects of idiosyncratic shocks depends not only on the type of shock but also on the size of the region directly affected. Chapter 3- We analyze in this chapter the macroeconomics effects of fiscal policy shocks in the Economic Community of West African States (ECOWAS). To that end, we use a Global Vector Autoregression (GVAR) model, which allows us to assess both the within country and the cross borders spillover effects of the fiscal shocks. For the dynamic analysis, we consider negative country-specific public spending and revenue shocks affecting Nigeria as well as regional public spending and revenue shocks affecting two groups of countries in the area, namely the West African Economic and Monetary Union (WAEMU) and the Rest of ECOWAS (RECOWAS). We provide evidence of considerable cross-country heterogeneity in fiscal spillovers; for instance, spillovers are high for fiscal shocks affecting Nigeria, while the cross-border spillover effects on Nigeria are weak for shocks affecting WAEMU and RECOWAS. Our results also suggest that fiscal policy is very relevant in stimulating real output in each of the ECOWAS countries but limited for the cross-country output stimulation.
Keywords: Monetary union; DSGE; Idiosyncratic shocks; GVAR; Fiscal policy